1996
DOI: 10.1183/09031936.96.09081619
|View full text |Cite
|
Sign up to set email alerts
|

Recycling of hard-core smokers with nicotine nasal spray

Abstract: The primary aim of this smoking cessation study was to evaluate the effect of long-term treatment with nicotine nasal spray in a group of hard-core smokers. A further aim was to compare the effect of ad libitum with fixed dosage of nasal nicotine spray.Eighty nine smokers, failures from two earlier studies with nicotine patches, were enrolled in an open smoking cessation study with nicotine nasal sprays, to be used ad libitum (n=45) or on a fixed schedule of 1 mg·h -1 during the day (n= 44).Carbon monoxide-ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 15 publications
1
17
1
Order By: Relevance
“…Lando, Pirie, Roski, McGovern, and Schmid (1996) reported that a telephone support intervention significantly increased recycling (quit attempts) but not abstinence. Tønnesen, Mikkelsen, Norregaard, and Jorgensen (1996) did not find an impressive effect of nicotine nasal spray (6% after 1 year) or nicotine patch (0%) (Tønnesen, Norregaard, Sawe, & Simonsen, 1993) for relapsed smokers. There has been speculation that lack of treatment effects could be related to enrollment of severely dependent smokers or prior treatment with intensive regimens that might mitigate the effectiveness of additional treatment.…”
Section: Discussionmentioning
confidence: 95%
“…Lando, Pirie, Roski, McGovern, and Schmid (1996) reported that a telephone support intervention significantly increased recycling (quit attempts) but not abstinence. Tønnesen, Mikkelsen, Norregaard, and Jorgensen (1996) did not find an impressive effect of nicotine nasal spray (6% after 1 year) or nicotine patch (0%) (Tønnesen, Norregaard, Sawe, & Simonsen, 1993) for relapsed smokers. There has been speculation that lack of treatment effects could be related to enrollment of severely dependent smokers or prior treatment with intensive regimens that might mitigate the effectiveness of additional treatment.…”
Section: Discussionmentioning
confidence: 95%
“…A related issue is that we have not identified the parameters governing any biological indicator that would signify therapeutic success. For example, keeping nicotine levels within a specified range or ensuring that cotinine levels do not dip below a certain level might greatly improve chances for success, but whether this would be the case is not known for certain, despite several studies having reported the degree of cotinine replacement attained (e.g., Hjalmarson, Franzon, Westin, & Wiklund, 1994;Hurt et al, 1998;Jones, Nguyen, & Man, 1998;Lerman et al, 2004;Sutherland et al, 1992;Tonnesen, Mikkelsen, Norregaard, & Jorgensen, 1996).…”
Section: Introductionmentioning
confidence: 96%
“…A variety of definitions have been put forth (Dijkstra, Bakker, & De Vries, 1997;Dijkstra & De Vries, 2000a, b;Emery, Gilpin, Ake, Farkas, & Pierce, 2000;Jarvis, Wardle, Waller, & Owen, 2003;Pierce, Davis, & Fiore, 1989a;Tonnesen, Mikkelsen, Norregaard, & Jorgensen, 1996), none of which appear to capture fully all individuals who might be considered hardcore smokers. How to best define subgroups of smokers, in particular those referred to as hardcore or recalcitrant smokers, remains a substantial challenge.…”
Section: Introductionmentioning
confidence: 97%